2018
DOI: 10.3389/fnint.2018.00012
|View full text |Cite
|
Sign up to set email alerts
|

Source Reconstruction of Brain Potentials Using Bayesian Model Averaging to Analyze Face Intra-Domain vs. Face-Occupation Cross-Domain Processing

Abstract: We investigated the neural correlates of the access to and retrieval of face structure information in contrast to those concerning the access to and retrieval of person-related verbal information, triggered by faces. We experimentally induced stimulus familiarity via a systematic learning procedure including faces with and without associated verbal information. Then, we recorded event-related potentials (ERPs) in both intra-domain (face-feature) and cross-domain (face-occupation) matching tasks while N400-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 109 publications
(154 reference statements)
2
4
0
Order By: Relevance
“…Consistent with our expectation and previous research (Alzueta et al., 2019; Feuerriegel et al., 2019; Hashemi et al., 2019; Herzmann, 2016; Huang et al., 2017; Mohr et al., 2018; Olivares et al., 2018; Özkaya & Yıldırım, 2018; Schweinberger & Neumann, 2016; Wiese et al., 2013), we observed that N250r and N400 activations seemed to represent, respectively, the processes of accessing a stored structural representation of a face and retrieving knowledge about a person from long-term memory. We observed that both familiar faces and familiar external feature faces were associated with reliable N250r activity for the positive-going sub-component of N250r over prefrontal and frontal regions, indicating that these two types of target faces could prompt the brain to match the input with a known face’s representation, as activated by the FRU, corresponding to similar findings of previous investigators who used famous/familiar faces as stimuli (Engst et al., 2006; Mohr et al., 2018; Nie, Li, et al., 2016; Nie, Ye, et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with our expectation and previous research (Alzueta et al., 2019; Feuerriegel et al., 2019; Hashemi et al., 2019; Herzmann, 2016; Huang et al., 2017; Mohr et al., 2018; Olivares et al., 2018; Özkaya & Yıldırım, 2018; Schweinberger & Neumann, 2016; Wiese et al., 2013), we observed that N250r and N400 activations seemed to represent, respectively, the processes of accessing a stored structural representation of a face and retrieving knowledge about a person from long-term memory. We observed that both familiar faces and familiar external feature faces were associated with reliable N250r activity for the positive-going sub-component of N250r over prefrontal and frontal regions, indicating that these two types of target faces could prompt the brain to match the input with a known face’s representation, as activated by the FRU, corresponding to similar findings of previous investigators who used famous/familiar faces as stimuli (Engst et al., 2006; Mohr et al., 2018; Nie, Li, et al., 2016; Nie, Ye, et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, all of our three types of targets (familiar faces, familiar internal feature faces, and familiar external feature faces) were associated with reliable N400 activity, consistent with findings from previous investigations with famous/familiar faces (Huang et al., 2017; Olivares et al., 2018; Özkaya & Yıldırım, 2018; Schweinberger & Neumann, 2016). As mentioned in our Introduction, the function of N400 activity is to trigger the PIN to access the semantic information about the person being identified by the FRU or to indicate the retrieval or activation of knowledge relevant to the faces from long-term memory during repetition priming (Huang et al., 2017; Olivares et al., 2018; Özkaya & Yıldırım, 2018; Schweinberger & Neumann, 2016). Thus, within the time course of such priming, the waveform differences between the presentations of primes and targets are all termed as N400, regardless of whether the amplitudes of the waveforms of the target stimuli are more positive- or negative-going than those of the primes (Schweinberger & Neumann, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…ERP studies found that the N170 component supports expert object categorization (Bentin et al, 1996; Maurer et al, 2008; Scott et al, 2006) while the N250 component supports expert object individuation (Gentile & Jansma, 2012; Rossion & Jacques, 2012; Scott et al, 2006). Because both ERP components are potentially generated at the fusiform gyrus (Bobes et al, 2019; Kaufmann et al, 2009; Olivares et al, 2018; Schweinberger et al, 2002), these results show that expert object recognition is supported by the higher visual cortex, in particular, the fusiform gyrus and the inferotemporal cortex.…”
Section: Introductionmentioning
confidence: 75%